A study of the lead-lag relationship between price change and trading volume in futures markets using high-frequency data. (2015) - Streeter, Denise W.; Najand, Mohammad; Dondeti, V. Reddy; Benton, James E.
This paper uses high-frequency, tick-level data to examine the causal relationship between price change, trading volume and volatility in the S&P 500 index futures market. Based on 327, 860 observations during the pre-2008 financial crisis period of 2005 through 2007, we find significant evidence of a bidirectional impact at up to three to four lags, in minutes, at the return level. Prior research that used daily data could not have captured this impact. At the volatility level, we find that volume has predictive power to forecast return volatility starting at lag three, which is consistent with the sequential information arrival hypothesis.